THE SILENT PANDEMIC: A COMPREHENSIVE ANALYSIS OF THE IMPACT OF AIR POLLUTION ON HUMAN HEALTH - Asatullyev Rustam Baxtiyorovich,; Sobirova Maftunaxon Azamatjon qizi, (TADQIQOTLAR, 2026)
Abstract: Air pollution is the world’s largest single environmental health risk, contributing  to  approximately  7  million  premature  deaths  annually.  This  article provides a systematic review of the impact of air pollution on human health, focusing on particulate matter (PM2.5 and PM10), nitrogen dioxide (NO2), ozone (O3), and other  toxic  gases.  The  analysis  covers  the  pathophysiology  of  exposure,  including oxidative stress and systemic inflammation, and details the clinical consequences for the  respiratory,  cardiovascular,  neurological,  metabolic,  and  reproductive  systems. Special attention is given to vulnerable populations, including children, the elderly, pregnant women, and socioeconomically disadvantaged communities. The article also discusses environmental justice issues, recent epidemiological findings, and evidence-based mitigation strategies. The review concludes that while air pollution remains a global health emergency, targeted policy interventions, technological innovation, and public health measures can substantially reduce the burden of disease.